A New Class of Injection Moulded Structural Biocomposites from PHBV Bioplastic and Carbon Fibre. Issue 7 (6th November 2012) - Reddy, Jeevan Prasad; Ahankari, Sandeep; Misra, Manjusri; Mohanty, Amar
Abstract Biocomposites from carbon fibre (CF) and poly(hydroxybutyrate‐co‐hydroxyvalerate) (PHBV) bioplastic were fabricated by extrusion followed by injection moulding. The effects of fibre length and fibre loading on the performance of PHBV/CF composites were investigated. The amount of CF (for both 150 µm and 6 mm length) was varied from 10 to 40 wt.‐%. The significant improvement in tensile strength (65%) and flexural strength (96%) was observed at 30 wt.‐% CF (6 mm length) loading. The heat deflection temperature (HDT) of the PHBV/CF composites increased by 32% compared to neat PHBV. The fibre–matrix interaction was analysed using scanning electron microscopy (SEM). The tensile modulus of the composites was evaluated theoretically by the rule of mixture and the Hirsch model. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>